Masupirdine (SUVN‐502) in combination with donepezil and memantine in moderate Alzheimer's disease: Effect of AD duration since diagnosis and patient's age on efficacy endpoints: Human/Human trials: Cognitive enhancement. (7th December 2020) - Nirogi, Ramakrishna; Shinde, Anil K; Benade, Vijay; Subramanian, Ramkumar; Bhyrapuneni, Gopinadh; Ravulu, Jyothsna; Jetta, Satish; Rasheed, Mohammed Abdul; Badange, Rajesh Kumar; Jasti, Venkat
Abstract: Background: Masupirdine (SUVN‐502), a selective 5‐hydroxytryptamine‐6 (5‐HT6) receptor antagonist is in clinical development for the treatment of moderate Alzheimer's disease (AD). Masupirdine was studied in a phase 2 POC, multicenter, randomized, double‐blind, parallel group, 26‐week, placebo‐controlled proof‐of‐concept study in patients with moderate AD receiving stable doses of donepezil and memantine. Method: A total of 564 moderate AD patients with MMSE scores between 12 ‐ 20 were randomized (1:1:1) to receive either 50 mg or 100 mg of masupirdine or placebo once daily for 26 weeks. The study recruited patients in the age range of 50‐85 years, both inclusive and AD duration since diagnosis of 1 year or more. The primary efficacy endpoint was change from baseline in the Alzheimer's Disease Assessment Scale ‐ Cognitive Subscale (ADAS‐Cog 11). In subgroup analyses, impact of AD duration since diagnosis and patient's age on the effects of masupirdine on the clinical functions were assessed using primary and secondary endpoints. To evaluate the effect of AD duration, subgroup analysis of different diagnosis durations at screening visit were performed. To evaluate the effect of patient's age, subgroup analysis of 50‐70 years and 71‐85 years of age at the screening visit, both inclusive were performed. Further stratification was carried out based on memantine plasma concentrations at week 26 in both the subgroups. Safety was assessed throughout the study. Result: Masupirdine slowed down the cognitive decline in patients with AD diagnosis duration of >3 years. Beneficial effects of masupirdine increased with increasing disease duration; longer the AD duration, better the effect. Patients aged 50 ‐ 70 years had better improvement with masupirdine treatment on efficacy endpoints (ADAS‐Cog 11, CDR‐SB, MMSE) compared to placebo; difference reached to the level of minimum clinically important difference for cognitive endpoints. Subgroup analyses suggest further exploration of masupirdine as a treatment option in patients where current therapy is not responding. Conclusion: Together with the safety profile of masupirdine, the outcome from these subgroup analyses supports the potential clinical utility of masupirdine in patients with AD.